80-GHz-band low-power sub-harmonic mixer IC with a bottom-LO-configuration in 130-nm SiGe BiCMOS. Issue 4 (28th March 2016) - Yang, Xin; Xu, Xiao; Shibata, Takayuki; Yoshimasu, Toshihiko
Abstract : In this paper, a W-band (80 GHz) sub-harmonic mixer (SHM) IC is designed, fabricated and measured in 130-nm SiGe BiCMOS technology. The presented SHM IC makes use of a common emitter common collector transistor pair structure with a bottom-LO-configuration to decrease the LO power requirement and a tail current source to flatten the conversion gain. On-chip Marchand balun is designed for W-band on-wafer measurements. The SHM IC presented in this paper has exhibited a conversion gain of 3.9 dB at 80 GHz RF signal with an LO power of only −7 dBm at 39.5 GHz. The mixer core consumes only 0.68 mA at a supply voltage of 3.3 V.